Output power regulation system for portable micro fuel cell systems - Zhong, Shaoxuan; Yuan, Weijian; Liu, Xiaoqiang; Cao, Jiamu; Zhang, Yufeng (Frontiers in Energy Research, 2023)
This paper presents an output power regulation system for micro fuel cells, to help enhance the stability of the fuel cell in a portable micro power system. A structure of MCU controlled DC-DC converter is proposed. Then, the output characteristics of a selected fuel cell stack and the DC-DC converter’s power control functions are estimated by a system level model. Based on the simulation results the model provides, a power regulation system is implemented and test shows it fulfills its intended function and regulated the output power to a fixed level of 5W to 40W with good efficiency.